1998
DOI: 10.1136/emj.15.5.334
|View full text |Cite
|
Sign up to set email alerts
|

Puffer fish poisoning.

Abstract: 1 Farhat SM, Schneider RC, Gray JM. Traumatic spinal extradural hematoma associated with cervical fractures in rheumatoid spondylitis. J Trauma 1973;13:591-9.2 Iplikcioglu AC, Bayar MA, Kokes F, et al. Magnetic resonance imaging in cervical trauma associated with ankylosing spondylitis: report of two cases. J Trauma 1994;36:412-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
(4 reference statements)
0
24
0
3
Order By: Relevance
“…TTX and STX act by blocking the extracellular-opening of the pore locus of voltage dependent sodium receptors, preventing depolarization and propagation of action potential in nerve cells. This action occurs in the peripheral motor, sensory and autonomic nerves 10,16 . TTX also acts by depressing the respiratory and vasomotor center of the encephalic trunk 4 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…TTX and STX act by blocking the extracellular-opening of the pore locus of voltage dependent sodium receptors, preventing depolarization and propagation of action potential in nerve cells. This action occurs in the peripheral motor, sensory and autonomic nerves 10,16 . TTX also acts by depressing the respiratory and vasomotor center of the encephalic trunk 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2). A study in Brazil identified the components responsible for toxicity in Colomesus asellus, a freshwater species found in the Amazon region, to be saxitoxin and gonyautoxin 4,10 , toxins associated with PSP and not TTX 23 . Another study of Sphoeroides spengleri, a species found along the Atlantic coast, detected TTX and analogues (anhydro-TTX, Tetrodonic Acid and 4-epi-TTX): OLIVEIRA et al (2003) 22 showed that TTX levels in muscle, skin, and viscera from fish of the Sphoeroides genus are high and a risk to consumers, whereas levels in Lagocephalus genus are low and in theory present a lower degree of risk.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations